Vitamin D deficiency and TB disease phenotype. Issue 12 (23rd September 2015) - Pareek, Manish; Innes, John; Sridhar, Saranya; Grass, Lisa; Connell, David; Woltmann, Gerrit; Wiselka, Martin; Martineau, Adrian R; Kon, Onn Min; Dedicoat, Martin; Lalvani, Ajit
Abstract : Background: Extrapulmonary TB is increasingly common, yet the determinants of the wide clinical spectrum of TB are poorly understood. Methods: We examined surveillance data (Birmingham, UK: 1980–2009 and USA Centers for Disease Control: 1993–2008) to identify demographic factors associated with extrapulmonary TB. We then directly tested association of these factors and serum 25-hydroxycholecalciferol (25(OH)D) concentration with extrapulmonary TB by multivariable analysis in a separate UK cohort. Results: Data were available for 10 152 and 277 013 TB cases for Birmingham and US, respectively. Local-born individuals of white ethnicity had a lower proportion of extrapulmonary disease when compared with local-born non-whites (p<0.0001); both groups had a lower proportion of extrapulmonary disease when compared with foreign-born non-whites (p<0.0001). In a separate UK cohort (n=462), individuals with extrapulmonary TB had lower mean serum 25(OH)D concentration than those with pulmonary TB (11.4 vs 15.2 nmol/L, respectively, p=0.0001). On multivariable analysis, vitamin D deficiency was strongly associated with extrapulmonary TB independently of ethnicity, gender and other factors. Doubling in serum 25(OH)D concentration conferred substantially reduced risk of extrapulmonary disease (OR 0.55, 95% CI 0.41 to 0.73). Conclusions: We identify vitamin D deficiency as a probable risk factor for extrapulmonary dissemination in TB, which may account for the associations of dark-skinned ethnicity and female gender with extrapulmonary disease. Our findings implicate vitamin D status in Mycobacterium tuberculosis containment in vivo and, given the high prevalence of deficiency, may inform development of novel TB prevention strategies.